2022
DOI: 10.1186/s12865-022-00479-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel 4 immune-related genes as diagnostic markers and correlated with immune infiltrates in major depressive disorder

Abstract: Background Immune response is prevalently related with major depressive disorder (MDD) pathophysiology. However, the study on the relationship between immune-related genes (IRGs) and immune infiltrates of MDD remains scarce. Methods We extracted expression data of 148 MDD patients from 2 cohorts, and systematically characterized differentially expressed IRGs by using limma package in R software. Then, the LASSO and multivariate logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In recent years, some researchers have identified biomarkers associated with immune infiltration for AD or MDD patients by bioinformatics analysis. For example, four immune-related genes were identified as diagnostic biomarkers of MDD and were associated with immune infiltration [ 39 ]. A recent study has identified and verified six immune-related genes in AD patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some researchers have identified biomarkers associated with immune infiltration for AD or MDD patients by bioinformatics analysis. For example, four immune-related genes were identified as diagnostic biomarkers of MDD and were associated with immune infiltration [ 39 ]. A recent study has identified and verified six immune-related genes in AD patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathophysiology of MDD remains unclear. Recently, high-throughput sequencing technologies have been used in many studies to elucidate the pathophysiological mechanisms of MDD and identify biomarkers for diagnosis [ 40 , 41 ]. However, most of these studies have focused on differences between patients with MDD and healthy controls, while few have examined differences between MDD subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using machine learning approaches, Zhao et al [ 20 ] found that classifiers for SVM , RF , CNN , and NB , as well as the AUC for SVM , RF , CNN , and NB were 0.84, 0.81, 0.73, and 0.83, respectively. Linna et al [ 21 ] applied four immune-related genes ( CD1C , SPP1 , CD3D , and CAMKK2 ), and it has shown a good diagnostic value in discriminating MDD from controls based on immune-related genes, with an AUC of 0.861. In contrast, we found four TRRDEGs with an AUC of >0.7 in two datasets.…”
Section: Discussionmentioning
confidence: 99%